(3EOGQI CShGb GdJLRFIs - (3SjO SGde(B, (3YQaIs ((3YeGf(B:s (3OGQ GdQGjI(B,s, 2009)
(3GdJLGQI GdGdcJQhfjI h YGbJgG HGdJLRFI , JLGQI GdLedI h GdJLRFI GdGdcJQhfjI , GdJLGQI aj NOeGJ GdJLRFI h GdGOGQI GdGdcJQhfjI , eGgjI GdeTQhY h cjajI GNJjGQ h JUeje GdehbY GdefGSH dg h Jehjdg , GOGQI YfGUQ GdeRjL GdJShjbj dJLGQI GdJLRFI , JLRFI GdShb (B.s
(3eQGLY U(B.273s
Keywords: (3GdCShGb GdJLGQjIs; (3GdEOGQIs; (3GdJLGQIs